PERBEDAAN INDEKS PRESTASI KUMULATIF (IPK) MAHASISWA ANTARA GAYA BELAJAR VISUAL, AUDITORIAL DAN KINESTETIK PADA PROGRAM STUDI PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS PGRI PALEMBANG - Zahruddin Hodsay (Pendidikan Ekonomi FKIP Universitas Sriwijaya, 2016)
Abstract : This research titled Differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang. The problem in this research was “whether or not differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang?”. The objective of this research was to find out whether or not Differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang. The method used comparative test over two averages and the approach used a quantitative approach. The data were collected by the documentation and questionnaires. The population of this research was 129 students were taken from the eighth level students PGRI University of Palembang academic year 2014/2015 and the sample of this research was 98 students. The data analysis used the comparative test over two averages.The result of this research was obtained a visual learning style 3.29, auditory learning style 3.23, and kinesthetic learning style 3.23. Hypothesis test used comparative over two averages Fcount 1.36 with standard error Ftable ? 0.05 find out 3.10. so 1.36 < 3.10 then Ha was rejected and Ho was accepted so no differences between Cumulative Grade Point Average (CGPA) and Learning Styles of Visual, Auditory and Kinesthetic to the Accounting Education Study Program Faculty of Teacher Training and Education PGRI University of Palembang.Abstrak : Masalah dalam penelitian ini adalah apakah terdapat perbedaan IPK mahasiswa antara gaya belajar visual, auditorial dan kinestetik pada Program Studi Pendidikan Akuntansi FKIP Universitas PGRI Palembang?. Tujuan diadakannya penelitian ini adalah untuk mengetahui perbedaan IPK mahasiswa antara gaya belajar visual, auditorial dan kinestetik pada Program Studi Pendidikan Akuntansi FKIP Universitas PGRI Palembang.Metode penelitian yang digunakan adalah metode uji komparatif lebih dari dua rata-rata dan pendekatan yang digunakan adalah pendekatan kuantitatif. Sumber data penelitian ini adalah dokumentasi dan angket/kuesioner. Populasi dalam penelitian ini adalah seluruh mahasiswa semester 8 tahun akademik 2014/2015 yang berjumlah 129 orang, sedangkan sampel berjumlah berjumlah 98 orang. Teknik analisis data yang digunakan adalah teknik analisis uji komparatif lebih dari dua rata-rata .Dari hasil penelitian diperoleh rata-rata IPK mahasiswa yang memiliki gaya belajar visual sebesar 3,29, mahasiswa yang memiliki gaya belajar auditorial sebesar 3,23 serta mahasiswa yang memiliki gaya belajar kinestetik sebesar 3,23. Sedangkan pengujian hipotesis dengan menggunakan uji komparatif lebih dari dua rata-rata diperoleh Fhitung yaitu 1,36 sedangkan Ftabel dengan taraf kesalahan ? 0,05 diperoleh yaitu 3,10. Jadi 1,36 < 3,10 maka Ha ditolak dan H0 diterima yang berarti tidak ada perbedaan IPK mahasiswa berdasarkan gaya belajar visual, auditorial dan kinestetik pada mahasiswa Progam Studi Pendidikan Akuntansi FKIP Universitas PGRI Palembang